(untitled) - Chau, K. T (Singapore, 2015)
Includes bibliographical references and index; Introduction -- DC Motor Drives -- Induction Motor Drives -- Permanent Magnet Brushless Motor Drives -- Switched Reluctance Motor Drives
Keywords: Electric vehicles -- Motors; Electric motors; Electric power transmission; Xe điện -- Động cơ; Động cơ điện; Truyền tải điện